Inovasi Pembelajaran Bahasa Indonesia SD dengan Metode Canvas (MBC): Meningkatkan Kemampuan Berbahasa dan Kreativitas Siswa Kelas 1 SD Islam Al Yaqut - Dedy Hendry; Bernadus Wahyudi Joko Santoso; Haryadi Haryadi (STKIP Subang, 2025)
This study aims to develop an innovative Indonesian language learning model based on the Canvas Method (MBC) to enhance the language abilities and creativity of first-grade students at SD Islam Al Yaqut. The innovation was initiated in response to students’ low proficiency in understanding simple texts, constructing meaningful sentences, and expressing ideas both visually and verbally. The Canvas Method integrates visual elements, exploration, and hands-on activities, making learning more concrete, engaging, and developmentally appropriate for children aged 6–7 years. This research employed a mixed-methods approach consisting of observation, product development, implementation, and reflection. The results indicate significant improvement in students’ language skills (listening, speaking, reading, and writing) as well as their creativity, reflected through the increased variety of ideas and visual representations produced on the canvas sheets. Therefore, the MBC is considered relevant and effective as an instructional innovation for Indonesian language learning in elementary schools